2021
DOI: 10.1371/journal.pone.0256382
|View full text |Cite
|
Sign up to set email alerts
|

A review of the effectiveness of operational curtailment for reducing bat fatalities at terrestrial wind farms in North America

Abstract: Curtailment of turbine operations during low wind conditions has become an operational minimization tactic to reduce bat mortality at terrestrial wind energy facilities. Site-specific studies have demonstrated that bat activity is higher during lower wind speeds and that operational curtailment can effectively reduce fatalities. However, the exact nature of the relationship between curtailment cut-in speed and bat fatality reduction remains unclear. To evaluate the efficacy of differing curtailment regimes in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…Turbines operate for half the time when the curtailment wind speed is the same as the median; although the result is a reduction in mortality risk, it does not indicate a causal relationship between bat activity or mortality and 5.5 m/s wind speed. We note that more recent studies have shown a consistent reduction in bat mortality for every 1 m/s increase in cut-in speed (50% reduction in [ 23 ], 33% reduction in [ 20 ]). A 40–60% reduction in mortality would be an outcome consistent with mortality being reduced because the turbines are curtailed about half the time.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Turbines operate for half the time when the curtailment wind speed is the same as the median; although the result is a reduction in mortality risk, it does not indicate a causal relationship between bat activity or mortality and 5.5 m/s wind speed. We note that more recent studies have shown a consistent reduction in bat mortality for every 1 m/s increase in cut-in speed (50% reduction in [ 23 ], 33% reduction in [ 20 ]). A 40–60% reduction in mortality would be an outcome consistent with mortality being reduced because the turbines are curtailed about half the time.…”
Section: Discussionsupporting
confidence: 54%
“…Curtailment based on wind speeds reduces, but does not eliminate, bat mortality at wind energy facilities [ 19 , 20 ]. Experimental studies show that reductions in mortality range from about 50–70% (e.g., 50–70% in Alberta [ 16 ]; 47% in West Virginia [ 21 ]; 62% in Vermont [ 22 ]; 63% throughout North American wind farms [ 23 ]).…”
Section: Introductionmentioning
confidence: 99%
“…High-risk areas are coasts and forested hills, whereas mortality is relatively low in agricultural areas further away from the coast [ 7 ]. Effective mitigation has been achieved by curtailment procedures that limit the production time of wind turbines [ 16 , 17 , 18 , 19 , 20 ]. Increasing the cut-in speed at which blades start rotating to wind speeds of 5 m/s has resulted in an average reduction of 62% in the number of fatalities [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reducing bat mortality at wind‐energy projects is of growing importance given the potential impacts of wind energy on tree bat populations (Frick et al 2017). Curtailment at wind speeds below 5.0 m/second reduces bat mortality from 42–78% (Arnett et al 2013 b , Hein et al 2014, Martin et al 2017, this study), and some evidence exists that greater reductions in bat fatalities can be achieved by curtailing operations at higher wind speeds (Good et al 2012, Arnett et al 2013 b , Adams et al 2021). Curtailment at higher wind speeds results in greater losses in energy production and may not be economically feasible at many wind‐energy projects.…”
Section: Discussionmentioning
confidence: 86%
“…Wind turbine curtailment, also known as blade feathering, is a strategy that prevents turbines from spinning at night at speeds >1–2 rotations/minute, when wind speeds are below a pre‐determined value. Wind turbine curtailment reduces fatalities of nearly all bat species affected by wind turbines (Arnett et al 2013 b , Martin et al 2017, Adams et al 2021). Curtailment (i.e., cut‐in speed curtailment) results in lost energy production at night and causes adverse impacts on wind project economics if not optimized.…”
mentioning
confidence: 99%